Acceleration of cardiac tissue simulation with graphic processing units. - Sato D; Xie Y; Weiss JN; Qu Z; Garfinkel A; Sanderson AR; Sato, Daisuke; Xie, Yuanfang; Weiss, James N; Qu, Zhilin; Garfinkel, Alan; Sanderson, Allen R (Medical & Biological Engineering & Computing, 2009)
In this technical note we show the promise of using graphic processing units (GPUs) to accelerate simulations of electrical wave propagation in cardiac tissue, one of the more demanding computational problems in cardiology. We have found that the computational speed of two-dimensional (2D) tissue simulations with a single commercially available GPU is about 30 times faster than with a single 2.0 GHz Advanced Micro Devices (AMD) Opteron processor. We have also simulated wave conduction in the three-dimensional (3D) anatomic heart with GPUs where we found the computational speed with a single GPU is 1.6 times slower than with a 32-central processing unit (CPU) Opteron cluster. However, a cluster with two or four GPUs is faster than the CPU-based cluster. These results demonstrate that a commodity personal computer is able to perform a whole heart simulation of electrical wave conduction within times that enable the investigators to interact more easily with their simulations.